(untitled) (Bangladesh Journal of Urology, 2020)
Objective: To compare the outcomes of tubularized incised plate urethroplasty and modified tubularized incised plate urethroplasty in the primary management of distal hypospadias Materials and Methods: Total 70 patients of age group 2 to 10 years with distal hypospadias were selected for this study from January 2008 to December 2010. They were divided into Group-A (n=35) treated by the tubularized incised plate urethroplasty and Group-B (n=35) treated by the modified tubularized incised plate urethroplasty.The modification was performed by using inner preputial skin on the incised plate before tubularization. All patients were followed up immediately and at 4th, 8th and 12th weeks after operation. Results: The satisfactory cosmetic and functional outcomes were observed in 29 patients (82.85%) of Group-A and all families of Group-B were happy with aesthetic and functional outcomes. Urethrocutaneous fistula developed in 5 patients (14.70%) patients of Group- A and 1 (2.94%) patient in Group-B. Three patients (8.82%) in group-A and one patient (2.94%) in group-B were found to develop meatal stenosis. One patient (2.94%) developed stricture urethra in group A but no patient in group-B developed urethral stricture. Overall complications occurred in 10 patients (29.41%) in Group-A and 2 patients (5.88%) in Group-B. Conclusions: This study demonstrates that modified tubularized incised plate urethroplasty had excellent cosmetic and functional outcomes and fewer complications than that of tubularized incised plate urethroplasty in the primary management of distal hypospadias. Bangladesh Journal of Urology, Vol. 17, No. 2, July 2014 p.75-81